Determination of Antioxidants by DPPH Scavenging Activity of Ashitaba Herb (Angelica keiskei) Methanol Extract - Handa Muliasari; Nisa Isneni Hanifa; Wahida Hajrin; Mahacita Andanalusia; Agriana Rosmalina Hidayati (Jurnal Biologi Tropis, 2023)
Ashitaba (Angelica keiskei) is one of the plants cultivated in the Sembalun region, Lombok, NTB, which has the potential to be developed as a source of antioxidants. This study aims to determine the antioxidant activity of the methanol extract of ashitaba herb by measuring the inhibition against DPPH (1,1-diphenyl-2-picrylhydrazyl) radicals using a UV-Vis spectrophotometer. Ashitaba herb samples were collected in Jorong Hamlet, Sembalun Bumbung Village, Sembalun District, East Lombok Regency at coordinates 8°23'5.273" LAT - l16°32'12.016" EAST. The sample was then processed into simplisia with a simplisia yield of 14.75%. The simplisia was dechlorinated with n-hexane solvent and then extracted with 80% methanol solvent using the sonic method, giving a methanol extract of ashitaba herb yielding 20.30%. DPPH radical inhibitory activity was measured at a maximum wavelength of 516 nm and an operating time (OT) of 30 minutes. The methanol extract of ashitaba herb has an IC50 value of 129.40 ± 7.36 ppm, which shows moderate antioxidant activity, with a standard compound comparison of ascorbic acid with an IC50 value of 2.37 ± 0.06 ppm, which is classified as very potent.